420- ±¬³. 1.1

download 420- ±¬³.  1.1

If you can't read please download the document

  • date post

    13-Sep-2014
  • Category

    Documents

  • view

    125
  • download

    1

Embed Size (px)

Transcript of 420- ±¬³. 1.1

11.1 . 17 - 18 A 1. f(x) = 3 3 . f(1), f(2) , f(-1) f(1) = 13 3 1 = 13 = -2 f(2) = 23 3 2 = 8 6 = 2 f(-1) = (1)3 3 (1) = 1 + 3 = 2 2. (t) = t2 5t + 6, (0) (1). t (t) = 0; (0) = 02 5 0 + 6 = 0 0 + 6 = 6 (1) = 12 5 1 + 6 = 1 5 + 6 = 2 (t) = 0 =

t2 5t + 6 = 0 t=

52 4. 1 6 = 25 24 = 1,

5 1 5 1 = = =3 2 2 2.1 2h(0)

3.

h() = ,

h(

2

) .

[0 , 2] h( )= 0; h(0) = 0 0 = 1 0 = 1

h ( ) = 0 = 0 = , = 0 = 0 , 0, = 1 = 1 = 4 = + , 4 5 = + = [0 , 2], =4 4 44. f(x) =

h( ) = = 0 1 = 1 2 2 2

1 2 ln , f(1) f(e) 2 f (e) = 1 1 ln e2 = 2ln e = 11=1 2 22 ; ( 1 2) )(

f (1 = )5.

1 1 1 ln12 = ln1 = 0 = 0 2 2 2

( 1)( 2) 0

f () =

1 0 2 0 1 2 =

{1 , 2}

6. f() = ( 3)( 7) ;

2)( () = ( 3 7) ;

f() = ( 3)( 7)

f() = 2 10 + 21

f() x f(x )

+

3 0

7 0

+ +

f() < 0 3 < < 7 )( () = ( 3 7) f() 0 3 . 7. ( 3)( 7) 0 ) = ( , 3] [7 , + 7. f() = 32 2 1 g() = 2 1 ,

f (x) + g(x)

, f(x) + g(x)

,

f(x) g(x)

f g Af = R g = R R f() + g() = (32 2 1) + (2 1) = 32 2 1 + 2 1 = 32 2 2

R

f()g() = (3 2 1)(2 1) = 63 32 42 + 2 2 + 1 = 63 72 + 1 g() 0

f (x) , g(x)

2 1 0

2 1

1 2

f (x) 3x2 2x 1 = g(x) 2x 1

8.

i ) lim ( x 2 3x + 4),x 0

ii)

x -2

lim [( 2 x 1)( x + 4)],x 4

iii) lim ( x + 1 ) x 4 x

iv ) lim ( 2 x + 3 x )x 0

, v) lim (3 x + x )

) )

lim x2 3x + 4) = 02 3 0 + 4 = 4 (x 0x2

lim[(2x 1 x + 4)] = ([2(2) 1 2 + 4)) = (4 1 2 + 4) = (5) 2 = 10 )( ]( )(1 1 1 5 ) = 4+ = 2+ = 2 2 x 4

) lim( x + x4 )x 0

lim(2 + 3 = 2 + 3 0 = 2 0 + 3 1 = 3 ) 0

39.

i ) lim

x -2

x 2 -4 3(x-2)2

iv ) lim x 16 x 4 x 4 i)

2 ii) lim 5x x -1 x 2 + 1 2 v) limx x 25 x -5 x + 5

iii) lim[( x + 1) x ]x 0 2 vi) lim 2 x 3x 2 x 2 x2

x2 4 (2) 2 4 4 4 0 = = = =0 x2 3 x 2 ( ) 3(2 2) 12 12 lim

ii) iii)

5x2 5(1 2 ) 5 = = 2 x1 x2 + 1 (1 +1 2 ) lim

lim x + 1 ] (0 + 1 0 = 1 1 = 1 [( ) = ) x0

iv)

lim lim x 16 = x 4 x 4 x 4

2

0 0

( x 4)( x + 4) lim = x 4 ( x + 4) = 4 + 4 = 8 x4

v)

0 2 ( x + 5)( x 5) lim x 25 0 lim = lim ( x 5) = 5 5 = 10 x 5 x + 5 x 5 x+5 = x 5

vi)

lim

2x2 3x 2 0 = x2 x 2 02x2 3x 2 = (x - 2)(2x + 1)2 (x 2)(2x + 1 ) = lim(2x + 1 = 2 2 + 1 = 5 ) lim 2 x 3x 2 = lim x2 x2 x 2 x 2 x2

:

1.

f (x) =

1 1+ e1 x

,

f(x) + f(x) = 1

f (x) + f (x) =

11 1+ e x

+

11 1+ e x

=

11 1+ ex

+

1 1+ 1 1 ex1

1

1=1 1+ ex

+

11 ex

=

11 1 + ex

+1

x + e 1

1 + ex =

1+ ex1 1+ ex

= 1

1 ex

2. 100 m . , .

4

+ 2 . 100 m, + 2 = 100 (1) . = . (1) =

100 2 100 100 2 ( ) = = 2 2

3. , , 20 cm . h, h . r r 2r . h + 2r = 20 (1) V=

r=(2)

20 h 2

(2)

r 2 h

V ( h ) = 20 h 2 = + . (1) =2rh =r2 . = 2rh + r2 . (3)

(

)

2

h

0 < h < 20

h = 20 2r (3) (r) = 2r(20 2r) + r20 < 2r < 20

(1) 4.

0 < r < 20 0 < r < 10 . 2 1 0

(r) = 2r(20 2r) + r2 0 < r 90,

(180 ) = ,

(1800 ) = .

() = () = 10

=

5 = 90, = () = () = 10 = 10. 1 = 10. 90 = 10 () = 10 00 < < 1800

=

1 ( ) ( ) = 1 10 10 = 50 , 2 200 < < 1800 .

() = 50,

5. i)

limx 5

x 5 = 1 x 5 2 5

ii) limh 0

1+ h 1 1 = h 2

x 5 0 lim ( x 5 )( x + 5 ) 0 = x 5 x 5 = x 5 ( x 5)( x + 5 ) x 5 1 1 1 lim = = lim = . x 5 x 5 ( x 5)( x + 5 ) 5+ 5 2 5 x+ 5i) lim

ii)

limh 0

1 + h 1 0 lim ( 1 + h 1)( 1 + h + 1) 0 h = h 0 h ( 1 + h + 1)=

h ( 1 + h + 1) 1+ h 1 = lim h o h ( 1 + h + 1) 1 1 1 = lim = = h 0 2 1+ h +1 1+ 0 +1h 0

lim

( 1 + h 1)( 1 + h + 1)

1.2 . 26 27 A 1. i) ii) f() = 3 + 1 g() = 2 + 5 = 3 = 2 = 4 9 + 3h + 1 9 1 = lim h 0 h

iii) () = 2 + 2 i) lim

f (3 + h ) f (3) 3(3 + h ) + 1 3 3 1 = lim h 0 h 0 h h

3h = lim = lim 3 = 3 h 0 h 0 h ii) lim g ( 2 + h ) g ( 2) ( 2 + h ) 2 + 5 ( 2) 2 5 = lim h 0 h 0 h h f (3)=3

6 4 4h + h + 5 4 5 = lim h 0 h 2 = lim 4 h + h h 0 h h ( 4 + h ) = lim = lim ( 4 + h ) = 4 h 0 h 0 h2

iii)

g(2)=-4

( 4 + h ) ( 4) ( 4 + h ) 2 + 2( 4 + h ) 16 8 lim = lim h 0 h 0 h h 2 16 + 8h + h + 8 + 2 h 16 8 = lim h 0 h 2 h + 10h = lim h 0 h h ( h + 10) = lim = lim ( h + 10) = 0 + 10 = 10 h 0 h 0 h (4) = 101 t =1 t +1

2.

f (t) =

1 1 f (1 + h ) f (1) lim = lim 1 + h + 1 1 + 1 h 0 h 0 h h 1 1 = 2+h 2 lim h 0 h 22h 2( 2 + h ) = lim h 0 h h 1 1 = lim 2 h ( 2 + h ) = lim 2( 2 + h ) = 4 h 0 h 0 f (1) = 1 4

3.ii)

i) L r L = 2r . L r r = 3 . r = r2 . r r = 2 .

i) L (3 + h ) L (3) 2 (3 + h ) 2 3 = lim h 0 h 0 h h 6 + 2 h 6 = lim 2 h = = lim h 0 h 0 h h 2 h = lim = lim (2) = 2. h 0 h 0 h L(3) = 2, L(3) = 2 lim

7 ii) E ( 2 + h ) E ( 2) ( 2 + h ) 2 22 = lim h 0 h 0 h h ( 4 + 4h + h 2 ) 4 = lim h 0 h 4 + 4 h + h 2 4 = lim h 0 h 4 h + h 2 = lim h 0 h h ( 4 + h ) = lim = lim ( 4 + h ) = 4 + . 0 = 4 h o h 0 h (2) = 4 lim

4.i) , , = 5 ii) V , , = 10 . i) lim () = 2

E (5 + h ) E (5) (5 + h ) 2 52 25 + 10h + h 2 25 = lim = lim h 0 h 0 h 0 h h h 2 h (10 + h ) 10h + h = lim = lim = lim (10 + h ) = 10 . h 0 h 0 h 0 h h , = 5, (5) = 10 ii) V() = 3 V (10 + h ) V (10) (10 + h ) 3 10 3 = lim = lim h 0 h 0 h h 2 3 3 h (300 + 30 h + h 2 ) lim 1000 + 300h + 30 h + h 10 = lim . h 0 h 0 h h 2 = lim (300 + 30 h + h ) = 300 + 30. 0 + 02 = 300 h 0 V(10) = 300 .

5. i) f(x) = x2 (3, f(3) ) ii) f(x) = 2 x (4 , f(4)) ( x 0 , f( x 0 )) y f( x 0 ) = f( x 0 )(x x 0 ) i) f (3 + h ) f (3) (3 + h ) 2 9 lim = lim h 0 h 0 h h

8 9 + 6h + h 9 = lim h 0 h h (6 + h ) = lim = lim (6 + h ) = 6 + 0 = 6 h 0 h 0 h f( x 0 ) = f(3) = 6, f( x 0 ) = f(3) = 32 = 9 2

y 9 = 6(x 3)

y 9 = 6x 18

y = 6x 9

ii) f( x 0 ) = f(4) = 2 4 = 2 2 = 4 f ( 4 + h ) f ( 4) 2 4+h 4 0 0 lim = lim h 0 h 0 = h h 4( 4 + h ) 16 ( 2 4 + h 4)( 2 4 + h + 4) = lim = lim h 0 h 0 h ( 2 4 + h + 4) h ( 2 4 + h + 4) 16 + 4 h 16 4h 4 = lim = = lim = h 0 h 0 h ( 2 4 + h + 4) h ( 2 4 + h + 4) 2 4+h +44 4 1 = = 4+ 4 8 2

f(4) =

1 2

y4=

1 ( x 4) 2

y= 1x+2 2

1.3 . 35 38 A ( 1 18)

1.i) f(x) = 5 ii) f(x) = x4 iii) f(x) = x9 i) f () = (5) = 0 ii) f () = (4) = 43 iii) f () = (9) = 98

2..i)

f() = 2'

3

ii)

f() = -3

iii)

f() = -5

3 1 3 3 1 3 i) f (x) = 2 = 2 = 2 2 2

ii) f() = ( -3) = 3 -3 1 = 3 - 4 iii) f () = ( -5) = 5 -5 - 1= 5 - 6

3.

9 i) f (x) = 3 x ii) f(x) = x5 ' 2

,

x>0

i) f () =

( )3

x

'

1 2 1 1 = x3 = 1 x3 = 1x 3 3 3 '

ii) f ( ) =

(

5

x

2

)

'

3 2 2 5 2 x5 1 = 2 x 5 = x = 5 5

1 4. i) f ( x ) = x '

ii)

f(x) = 1 3 x

iii) f(x) = 1 , 5 x2

>0

' 3 1 1 21 =x = 1 x 2 i) = 1 2 x x2 ' ' 1 ' 4 1 1 3 1 3 x ii) 3 = 1 = x = 3 x 3 x '' ' 7 1 1 52 = 2 = x = 2x 5 iii) 5 2 5 x x5 '

5.i) f(x) = 4x3 i) (43)= 12x2 ii) (6 -5) = 30x - 6 iii) - 2 x 20 5

ii) f(x) = 6x -5

2 20 iii) f ( x ) = x 5

(

) = 40 x 5'

19

= 8 x19 ii) f(x) = 6x x

6 6.i) f ( x ) = 4 i)

x'

, >0

5 1 ' 1 -6 = 6 = 6 x 4 = 6 x 4 1 = 3 x 4 4 1 4 2 x x4 '

ii) 6 x x

(

)

'

1 1 1 3 = 6x x 2 = 6x 2 = 18 x 2 = 9 x 2 2 2 iii) f(x) = x + 2x-1 x

'

'

7.i) f(x) = x4 + 3x2 i)

3 2 ii) f ( x ) = x + 5 + x

f(x) = (x4 + 3x2) = (x4) + (3x2) = 4x3 + 6x

ii) f(x) = x 2 + 5 + 3 = ( x 2 + 5 + 3x 1 ) x = (x2)+ (5) + (3x -1) = 2x + 0 3x -2 = 2x 3x -2 2 2 iii) f(x) = x + 2 x 1 = x + 2 x 1 x x x x 2 = x + 2x 1 x x x = ( x + 2 x 1 )' ' ' '

(

)

10'

= ( x ) + ( 2) ( x 1 ) = 1 + 0 + -2 = 1 + -2 .

8.i) f(x) = 8x3 x + 5 ii) f(x) = 6x 8(x2 + x) i) f(x) = (8x3 x + 5) = (8x3) (x) + (5) = 24x2 x ii) f(x) = (6x 8(x2+x)) = (6x 8x2 8x) = (6x) (8x2) (8x) = 6x 16x 8

9.i) f() = (3 + 1)(4 + 1) ii) f() = (1 ) i) f(x) = (3 + 1)(4 + 1) = 7 + 4 + 3 + 1 f() = (7 + 4 + 3 + 1) = 76 + 43 + 32

ii) f() = (1 ) = f () = ( )= () () = [() + ()] = ( ) = (2 2) = 2

10.i) f() = + 3( + 1)( 1) ii) f() = 42 32

11 i) f() = + 3( + 1)( 1) = + 32 3 f() = ( 32 3) = () (3